Identification of a fragment of the internal transcribed spacer region of rDNA in Cenchrus purpureus (Poaceae) - Hernández Montesinos, A.R.; Recio, María E.; Carvajal Yepes, Mónica; Arango, J.; Rodríguez Alfonso, Daymara; Fortes González, Dayleni; Herrera García, R.S. (Cuban Journal of Agricultural Science, 2025)
The internal transcribed spacer (ITS) region is easy to amplify due to its numerous copies present in the plant genome, but there in not researchers of this region in the forage species Cenchrus purpureus. This study aimed to identify by Polymerase Chain Reaction (PCR) a fragment of the ITS region of the ribosomal DNA of the nucleus in C. purpureus using the primers ITS1/ITS4 and compare it with two samples of Urochloa spp. The molecular study used DNA samples from 62 C. purpureus accessions from the grass and forage germplasm bank belonging to Instituto de Ciencia Animal and two samples of Urochloa spp. accessions from the Genetic Resources Program of the Alliance of International Bioversity and the International Center for Tropical Agriculture. The DNA from the 62 C. purpureus accessions and Urochloa spp. controls were amplified with ITS1/ITS4 primers. The amplification products revealed a clear polymorphic band in the gels for each accession and an approximate size of 1000 bp in C. purpureus and 850 bp in Urochloa spp. The primers determined differences in amplifications between samples of C. purpureus and Urochloa spp. although they did not show variability between accessions of the same species. These molecular markers can be used to verify PCR amplification of C. purpureus DNA samples and to differentiate species in Poaceae genera.